1963
DOI: 10.1161/01.res.13.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrhythmias Following Condenser Discharges and Their Dependence Upon Strength of Current and Phases of Cardiac Cycle

Abstract: With the technical assistance of Z. Blaxek, M. R6bl, and E. Sladkova and the statistical evaluation of Z. Roth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
1

Year Published

1964
1964
1987
1987

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…Accepted for publication July 1, 1968. capacitor discharges through the chest (1). In later papers he extended this study to include discharges in which an inductor was inserted in series with the capacitor (2,3).…”
Section: Additional Abstractmentioning
confidence: 99%
“…Accepted for publication July 1, 1968. capacitor discharges through the chest (1). In later papers he extended this study to include discharges in which an inductor was inserted in series with the capacitor (2,3).…”
Section: Additional Abstractmentioning
confidence: 99%
“…Previous work 1 --has shown the necessity of selecting, for the discharge circuit, parameters that will keep voltage as low as possible, but many questions concerning the optimal parameters for d-c condenser discharges still remain unanswered. Gurvic 3 has described a major portion of existing information on this subject, and Mackay and Leeds 4 have studied optimal parameters for condenser discharges up to 15 microfarads (/AF).…”
mentioning
confidence: 99%
“…These values are interrelated, but some are of greater biological importance than others for the given objective. On the basis of our previous results 1 ' '-• 1S we can define the optimal defibrillation impulse as that which produces the least functional and morphological damage to the myocardium. The relative importance of the various physical parameters would appear to be: 1) minimal voltage and current, and 2) minimal delivered electrical energy.…”
mentioning
confidence: 99%
“…However, Del Guerico et al,-have observed low cardiac output in three patients undergoing external cardiac massage. Alexander et al 8 reported successful treatment of ventricular tachycardia by transthoracic electric shock in 1961. Their paper was followed by others, particularly from Lown's group *~° which described the successful use of transthoracic shock for terminating a variety of other cardiac arrhythmias.…”
mentioning
confidence: 99%
“…In another study, Lown and associates 4 " used a single capacitor which discharged through the chest via a series inductor. Peleska 8 has published a detailed experimental study of the factors which cause certain types of capacitor discharges to "damage" the heart, as indicated by the observation that subsequent defibrillation was more difficult. Numerous other investigators have contributed also to our understanding of the use of capacitor discharges in the treatment of ventricular fibrillation.…”
mentioning
confidence: 99%